Criminology - Glick, Leonard (Allyn & Bacon, 2008)
"Criminology," 2n edition is the most accessible, hands-on introductory textbook on the market. The author uses a unique method for organizing the material in this manageable, 14-chapter textbook. A student-friendly format -- bulleted lists, summary statements, a running glossary, and a built-in study guide -- prepare students for success.